It's okay to be the boss : the step-by-step guide to becoming the manager your employees need - Tulgan, Bruce (New York : HarperCollins, 2007)
Management trainer Tulgan puts his finger on the biggest problem in corporate America--an undermanagement epidemic affecting managers at all levels--and offers another way. His clear, step-by-step guide to becoming the strong manager employees need challenges bosses everywhere to spell out expectations, tell employees exactly what to do and how to do it, monitor and measure performance constantly, and correct failure quickly and reward success even more quickly. Now that's how you set employees up for success and help them earn what they need. Tulgan opens our eyes to the undisciplined workplace that is overwhelming managers and frustrating workers and invites bosses everywhere to accept the sacred responsibility of managing people. His message: It's okay to be the boss. Be a great one!--From publisher description.
The undermanagement epidemic -- Get in the habit of managing every day -- Learn to talk like a performance coach -- Take it one person at a time -- Make accountability a real process -- Tell people what to do and how to do it -- Track performance every step of the way -- Solve small problems before they turn into big problems -- Do more for some people and less for others.
Includes index.
Keywords: Executives; Leadership